Christmas wife - Jones, David, 1934-2008; Robards, Jason; Harris, Julie, 1925-2013; Norris, Helen, 1916-; Cinetel Films (New York : Polymuse, Inc., 1988)
Recently widowed John Tanner, not wanting to spend Christmas alone, decides to seek companionship through a "social introductions" agency. He meets Iris who, though shy and reserved, agrees to join him. Soon a warm relationship develops, but there is a secret side to Iris that, when revealed, will change both their lifes forever.
Based on the short story by Helen Norris.
Jason Robards, Julie Harris, Don Francks, James Eckhouse.
Director of photography, Brian West; editor, Ruth Foster; music, Max Harris.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Widowers -- Drama; Friendship -- Drama; Christmas stories; Christmas films; Internet videos; Streaming video